1987
DOI: 10.1152/jappl.1987.62.3.1006
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of superior vena caval pressure increases extravascular lung water after endotoxemia

Abstract: In many sheep Escherichia coli endotoxin results in pulmonary hypertension, increased microvascular permeability, pulmonary edema, and increased central venous pressure. Since lung lymph drains into the systemic veins, increases in venous pressure may impair lymph flow sufficiently to enhance the accumulation of extravascular fluid. We tested the hypothesis that, following endotoxin, elevating the venous pressure would increase extravascular fluid. Thirteen sheep were chronically instrumented with catheters to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our data indicated that only interstitial edema developed with a 20% increase in extravascular lung water. These results are similar to data reported by Allen et al (22) who elevated both left atrial and cranial vena caval pressure in unanesthetized sheep that had received 4 ,ug/kg ofintravenous E. coli endotoxin. When left atrial pressure was raised to 13 mmHg and cranial vena caval pressure to 17 mmHg, extravascular lung water increased only to 5.2±0.1 g H20/g dry lung.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicated that only interstitial edema developed with a 20% increase in extravascular lung water. These results are similar to data reported by Allen et al (22) who elevated both left atrial and cranial vena caval pressure in unanesthetized sheep that had received 4 ,ug/kg ofintravenous E. coli endotoxin. When left atrial pressure was raised to 13 mmHg and cranial vena caval pressure to 17 mmHg, extravascular lung water increased only to 5.2±0.1 g H20/g dry lung.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that CVP better predicted EVLW than did PAOP, in conjunction with COP, may relate to the small numbers of EVLW or greater importance of CVP. Indeed, systemic venous pressure is the back pressure for lymphatic flow from the lungs, so that an elevated pressure contributes to pulmonary oedema, evoked by increased permeability, increased hydrostatic pressures, or both (40). The COP–PAOP gradient has been proposed as the intravascular filtration pressure linked to the development of pulmonary oedema, even though the level of the effective hydrostatic filtration pressure is somewhere between MPAP and PAOP and may be relatively independent of PAOP (6, 8, 11, 12, 26, 34, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation and dobutamine decrease the pulmonary capillary pressure and the central venous pressure. The decrease in the pulmonary capillary pressure prevents the pulmonary edema formation while the decrease in central venous pressure should increase the lung lymph flow and hence the removal of fluid from the interstitium into the systemic veins [88].…”
Section: Saudi Arabiamentioning
confidence: 99%